Representation of a Moorish Woman in a graffiti from Albayzin (Granada) - Barrera Maturana, José Ignacio (Anaquel de Estudios Árabes, 2007)
This paper studies a graffiti found in a Moorish house at Albayzín that represents a feminine figure. From her clothes and adornments, we believe she is a Moorish woman from the 16th century. Our aim is to contribute new data that can be useful to researchers of Andalusi medieval clothes. Also, we insist on the need to preserve and conduct serious studies of these manifestations, since sometimes they can provide us with interesting data about different aspects of Andalusi History.